Mentoring and Improving Knowledge on the Benefits of Garlic in Reducing Blood Cholesterol Levels among Hypertensive Prolanis Members - Anik Handayati; Suhariyadi Suhariyadi; Pestariati Pestariati (Frontiers in Community Service and Empowerment, 2026)
Hypertension is a non-communicable disease that is a major cause of stroke and coronary heart disease. It is commonly found in the community and is a significant contributor to mortality and disability worldwide. A preliminary study showed that more than 50% of Prolanis members in Bangsah Village, Sreseh Subdistrict, Sampang Regency had high cholesterol levels; therefore, alternative supplements are needed to reduce blood cholesterol levels. Garlic is a food ingredient that is widely available in the community but has not been widely utilized as a cholesterol-lowering supplement. Garlic contains allicin, which has strong antimicrobial, anti-inflammatory, and antioxidant properties. It also contains ajoene, saponins, flavonoids, and various sulfur compounds that contribute to its health benefits. Studies have shown that garlic consumption can help reduce total cholesterol and LDL levels. Therefore, education on processing garlic into black garlic is highly needed to reduce cholesterol levels among hypertensive Prolanis members. The results of the community service activity showed that the program was implemented smoothly and successfully, starting from the survey and coordination stage, the initial assessment, program implementation, and evaluation. The success of this PKM activity is expected to be beneficial for the wider community, especially regarding the use of garlic to reduce cholesterol levels. The evaluation results showed a 17% reduction in the number of hypertensive Prolanis members with high cholesterol levels.